Oven Pintar Berbasis Kontrol Elektonik Modul untuk Pengeringan Bahan Praktek di Laboratorium Pengecatan - Anton Hartanto; Hendra Saputra Pratama; Jody Suryanto (UPT Laboratorium Terpadu, Universitas Diponegoro, 2023)
Extreme climate change makes the situation and environmental conditions uncertain, causing the painting practice lecture process to be less than optimal. Weather that tends to be cloudy has the potential to damage the paint from student practicum results. Referring to these problems, in this research an LPG-assisted automatic paint dryer was made as the solution offered. The purpose of this research is to make an oven to support the acceleration of drying of student paint. This research is a design type, which is carried out to support effective and efficient learning in accordance with the planned learning series. The instruments used in this study were: (1) paint drying oven machine assessment sheet; and (2) the target audience's response questionnaire. Indicators of research success are based on process and results. This smart oven based on electronic control module is very suitable to be used as a tool in improving the quality of painting results, especially in automotive painting. Making a smart oven based on electronic control of this module does not require too much money and is very easy to understand in operating the system because of the simplicity of how the oven machine system works. Questionnaire responses of students who have used smart ovens show results that agree and strongly agree with the existence of this smart oven.Â Â Â